GAMBARAN KEAMANAN PADA PASIEN KANKER YANG MENDAPATKAN KEMOTERAPI ORAL DI RUMAH - Nurwahida, Nurwahida; Huda, Nurul; Karim, Darwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Oral chemotherapy is a kind of cancer treatment which were formed in pills, capsules or liquids. This study aims to determine the patients safety of cancer who undergoing oral chemotherapy at home with descriptive research design using cross sectional approach. Sampling method was purposive sampling with total sample 41 people. The measuring instrument used is a questionnaire that has been tested for validity and reliability. The data analysis used univariate analysis. The result of research showed that the characteristic of the respondents were mostly at the age of 45-54 year amounted to 22 people (53,7%), the highest level of education were elementary school were 20 people (48,8%). The results showed that the majority of respondents managed oral chemotherapy at home with it was not safe of 90.2%, from each of components oral chemotherapy management only storage oral chemotherapy measures that most respondents manage safety by 95.1%, while other components more than 50% of respondents administer oral chemotherapy at home with not safety, namely the handling of oral chemotherapy of 92.7%, components oral administration of 58.5%, and components disposal waste oral of 95.1%. The results of this study recommend health workers to paid more attention to and provided health education to patients undergoing oral chemotherapy to managed their oral chemotherapy safety at home. Keywords: Cancer, Oral chemotherapy, Safety